2011
DOI: 10.1186/1471-2261-11-21
|View full text |Cite
|
Sign up to set email alerts
|

The impact of personality factors on delay in seeking treatment of acute myocardial infarction

Abstract: BackgroundEarly hospital arrival and rapid intervention for acute myocardial infarction is essential for a successful outcome. Several studies have been unable to identify explanatory factors that slowed decision time. The present study examines whether personality, psychosocial factors, and coping strategies might explain differences in time delay from onset of symptoms of acute myocardial infarction to arrival at a hospital emergency room.MethodsQuestionnaires on coping strategies, personality dimensions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…This study is part of a prospective longitudinal cohort study, the SECAMI study. 17,19 The aim of the SECAMI study was to investigate patients with MI, with focus on personality and psychological factors and their relation to prognosis, adherence to secondary prevention and treatment. The study base consisted of all patients with a diagnosis of acute MI who were admitted to the coronary care unit (CCU) at the Cardiology Department, Malmö University Hospital, between July 2002 and January 2005, and who fulfilled the inclusion criteria: 1) acute MI diagnosed by the definition by the European Society of Cardiology guidelines (International Classification of Diseases 10 code I21), 22 2) had knowledge of the Swedish language, 3) living within the hospital catchment area and 4) aged between 18 and 70 years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is part of a prospective longitudinal cohort study, the SECAMI study. 17,19 The aim of the SECAMI study was to investigate patients with MI, with focus on personality and psychological factors and their relation to prognosis, adherence to secondary prevention and treatment. The study base consisted of all patients with a diagnosis of acute MI who were admitted to the coronary care unit (CCU) at the Cardiology Department, Malmö University Hospital, between July 2002 and January 2005, and who fulfilled the inclusion criteria: 1) acute MI diagnosed by the definition by the European Society of Cardiology guidelines (International Classification of Diseases 10 code I21), 22 2) had knowledge of the Swedish language, 3) living within the hospital catchment area and 4) aged between 18 and 70 years.…”
Section: Methodsmentioning
confidence: 99%
“…18 On the other hand, neither coping strategies nor personality factors were related to delay time for seeking acute hospital care when the individual had difficult chest pain. 19 Personality factors have been shown to be directly related to the risk of CHD and this might influence health care utilization as well. 20,21 To our knowledge there are no studies where personality factors have been analysed in relation to health care utilization after an MI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some [41] but not all [42] studies have reported that depression is associated with a delay in seeking treatment for MI symptoms. At the same time, studies show that during MI, ET-1 is secreted in a dynamic fashion, being markedly elevated within hours following MI and peaking at 6 hours [40].…”
Section: Limitationsmentioning
confidence: 99%
“…Thus, psychological variables such as alexithymia influencing the decision may be relevant. Unfortunately many of the findings with respect to psychosocial factors in delayed care seeking are still controversial [3]. We sought to explore psychological factors that might explain the delay in seeking care in STEMI with particular attention to alexithymia.…”
Section: Tablementioning
confidence: 99%